Sol–gel chemistry in molten Brønsted acids towards "activated" carbons and beyond. Issue 27 (3rd July 2019) - Koyutürk, Burak; Evans, Josh; Multhaupt, Hendrik; Selve, Sören; Simke, Jan Ron Justin; Wark, Michael; Fellinger, Tim-Patrick
Abstract : Chemical activation of carbons is usually assigned to an oxidative and dehydrating nature of activating agents. We herein suggest that activating agents rather act as high temperature solvents and the porosity is developed by carbon phase separation. Abstract : "Chemical activation" using Brønsted acids as chemical agents is widely used to generate activated carbons for various sorption applications. Commercially relevant is especially a process using phosphoric acid as activating agent applied to abundant and inexpensive biomass such as wood or coconut shells. In this manuscript, we revisit the porogenesis mechanism based on experiments involving molecular model compounds and oxygen-free polymer precursors, as well as different molten acids as activating agents. Describing acid activation with principles of sol–gel chemistry results in a more general understanding and uncovers a versatile synthetic tool for materials nanochemistry.